DESIGNING AND BUILDING A WATER LEVEL CONTROL DISPLAY BY IMPLEMENTING WATER CONDUCTIVITY AND MICROCONTROLLER - Elroy Neil Sudiro; Anthony Riman; Eric Jobiliong (Cylinder : Jurnal Ilmiah Teknik Mesin, 2014)
Buoy is used to control water level in a water storage tank. However, this system has several weakness due to various problems of the mechanical parts, causing it to lose control. The purpose of this research is to design and build a water level control system display by employing water conductivity and microcontroller which is able to overcome the disadvantages of the mechanical system. The proposed system uses three wires as sensors. This report discusses the materials needed, the way of development, and the changes from the previous system design in the earlieast study to the final system. Based on the research conducted, the advantages of this system are the ability to use water from multiple sources, and through the usage of solenoid valves it can operate fully automatic. The disadvantage is that relatively long to drain due to the small aperture of the valve.